(untitled) (Asian Journal of Medical and Biological Research, 2025)
Feline panleukopenia is a highly transmissible and often fatal viral disease that particularly affects kittens. This study aimed to determine the prevalence of feline panleukopenia virus (FPV) among cats and evaluate associated risk factors. A cross-sectional study was conducted on clinically suspected cases from a selected region of Bangladesh. Data were collected using a structured questionnaire, and FPV infection was confirmed through clinical signs and rapid diagnostic tests. Fisher’s exact test was employed for statistical analysis to assess the associations. A total of 1,116 cat cases were retrieved, of which 262 were clinically diagnosed with FPV, resulting in an overall prevalence rate of 23.48%. FPV cases were most commonly observed in young, male, non-immunized Persian cats during the winter season. The highest prevalence was recorded in Persian breeds (30.25%), cats aged 0–6 months (29.46%), males (23.98%), during winter (26.22%), and in non-vaccinated cats (27.97%). These findings indicate a significant burden of FPV in the study area, underscoring the importance of future nationwide surveillance. The study highlights the critical need for targeted vaccination programs, early diagnosis, and preventive measures—particularly for young, non-vaccinated, and high-risk breeds—to reduce FPV incidence and mortality in cats. These findings can inform public health strategies and guide future nationwide surveillance efforts in Bangladesh. Asian J. Med. Biol. Res. 2025, 11(4), 135-142